Application of Standard Technique of Interoperability of Reuse of Information Resources in the catalogues of public information of the autonomous communities - Martín-González, Yolanda; Sainz-Iglesias, Paula (Revista General de Información y Documentación, 2015)
The purpose of this paper is to draw up a study on the application that performs the standard technique of interoperability of reusability of information resources with respect to the description of open data of the autonomous communities in Spain. Constituted the sample of the study the twelve catalogues of public information implemented by these administrations. Based on the observation of the entry of catalog pages and data sheets, initiated in October 2014 and finished in April 2015, was a descriptive-comparative analysis of the allocation of the metadata describing resources.The results suggest that autonomic catalogs meet partially the requirements demanded by the cited standard as regards the inclusion of the required metadata and heterogeneity in the designation of the metadata - additional and mandatory - there is also making it difficult to some extent to the recovery of the information required by the user.